The Role of Off-Farm Labor Participation Decisions of Married Farm Couples on Farm Direct Marketing in Taiwan - Chang H. (2017)
© 2017 Institute of Developing Economies Direct marketing from farm producers to consumers has been seen as a viable business option to increase farm income. This study investigates the factors that determine a farm's direct marketing decisions; special attention is paid to understanding the correlation between farm couples' off-farm labor participation and the farm's adoption of direct marketing strategies. A nationally representative dataset of 3,670 married family farm couples in Taiwan is used as an illustration. A multiple choice treatment effect model is estimated to cope with endogeneity bias. The results indicate a significant association between farm couples' off-farm labor decisions and the farm's adoption of direct marketing strategies. Moreover, gender difference is evident: farm husband's (wife's) off-farm work is positively (negatively) associated with the farm's direct marketing decision.